CHANGES OF LIP MORPHOLOGY IN RELATION TO DIFFERENT SKELETAL INDEX: IN MALAYSIAN MALAY AND MALAYSIAN CHINESE POPULATION - MOHAMMAD KHURSHEED ALAM; SHIFAT A NOWRIN; ASILAH YUSOF; BASARUDDIN AHMAD (International Journal of Pharma and Bio Sciences, 2015)
The main objective of this study is to evaluate the lip morphology changes in relation to different skeletal index between Malaysian Malay and Malaysian Chinese population. A total of 140 subjects were divided into Malaysian Malay and Malaysian Chinese groups. Each group consists of 70 males and females with all skeletal classes of malocclusions. Cephalometric radiograph were taken from subjects 56 males and 84 females with the age range 18 to 25 years. Cephalometric linear and angular measurements were carried out in relation to skeletal index and lip morphology. Descriptive statistics, racial and sexual dimorphism were evaluated. Three out of fourteen lip morphology variables showed significant difference between this two ethnic group and five out of fourteen lip morphology variables showed the differences between males and females. Changes in skeletal index associated with changes in lip morphology were found which considered as an important factor in orthodontic diagnosis and treatment planning.